PERBANDINGAN METODE FUZZY TSUKAMOTO DAN MAMDANI UNTUK MEREKOMENDASI NILAI SIMPANAN TABUNGAN BERDASARKAN SALDO RATA-RATA HARIAN PADA KOPERASI JASA KEUANGAN SYARIAH (STUDI KASUS DI BMT BINA IHSANUL FIKRI) - Omara, Safik; Honggowibowo, Anton Setiawan; Wintolo, Hero (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2012)
Funding accumulation should be designed to attract people to save in the institution money islamic. Savings Islamic investment is to apply the system to yield a return on investment. The value of customer revenue will never be the same each month even though they are the same a mount. Therefore, we need an alternative form of information storage decisions to be based recommendations for the specific results. For the results calculated by the method of the average daily balance is multiplied by other factors such as per classification average balance bank of funds, and the ratio(%). The average balance is the accumulation of sediment balance is divided by the number of days in a month. The application of fuzzy inference systems Tsukamoto and madman will be compared to the recommended savings will be applied to the system. Fuzzy logic has a degree of membership that represented the values 0 and 1, to be more balanced in the calculation is limited by certain factors. Factors include the amount of sediment balance and sediment balance your time to calculate the value of savings products or recommendations.Application of fuzzy Tsukamoto and Mamdani gives an overview of the differences indetermining the final outcome of the process defuzzifikasi, so that the known method is more suitable for recommending the value of deposits with a limited output of certain values (lower and upper limit of deposits). Fuzzy calculations have been tested with analysis of mathematical calculations manually and generate the same value.ListenRead phonetically